2006
DOI: 10.1121/1.2161427
|View full text |Cite
|
Sign up to set email alerts
|

Training the perception of Hindi dental and retroflex stops by native speakers of American English and Japanese

Abstract: Perception of second language speech sounds is influenced by one's first language. For example, speakers of American English have difficulty perceiving dental versus retroflex stop consonants in Hindi although English has both dental and retroflex allophones of alveolar stops. Japanese, unlike English, has a contrast similar to Hindi, specifically, the Japanese /d/ versus the flapped /r/ which is sometimes produced as a retroflex. This study compared American and Japanese speakers' identification of the Hindi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 54 publications
(52 reference statements)
4
54
0
Order By: Relevance
“…Previous research has demonstrated that allophonic experience from learners' native language improves both perception of non-native contrasts as well as their learning. (Best and Strange 1992;Halle et al 1999;Jamieson and Moroson 1986;Jenkins and Yeni-Komshian 1995;Kondaurova and Francis 2008;McAllister et al 2002;McClaskey et al 1983;Pisoni et al 1982;Pruitt et al 2006). The current results suggest that such experience also contributes to imitation.…”
Section: Does the Type Of A Sequence -Same Place Of Articulation Vs supporting
confidence: 50%
“…Previous research has demonstrated that allophonic experience from learners' native language improves both perception of non-native contrasts as well as their learning. (Best and Strange 1992;Halle et al 1999;Jamieson and Moroson 1986;Jenkins and Yeni-Komshian 1995;Kondaurova and Francis 2008;McAllister et al 2002;McClaskey et al 1983;Pisoni et al 1982;Pruitt et al 2006). The current results suggest that such experience also contributes to imitation.…”
Section: Does the Type Of A Sequence -Same Place Of Articulation Vs supporting
confidence: 50%
“…Also, consistent with this, there was evidence for a relationship between the amount of improvement on identification and discrimination tasks across participants, showing that people who improve on one are likely to improve on the other, and vice versa. Previous laboratory studies have shown that training using naturalistic exemplars is effective under task or stimulus conditions that place relatively lesser demands on working memory (Pruitt et al, 1990;Pruitt et al, 2006;Werker & Tees, 1984b). Other studies, however, have not successfully shown a training-related improvement in the perception of this contrast (Tees & Werker, 1984;Werker & Tees, 1984a;Werker et al, 1981).…”
Section: Discussionmentioning
confidence: 89%
“…As a result, adult English listeners assimilate the alveolar and retroflex sounds such that they perceive both sounds as instances of the alveolar consonant (Polka, 1991;RiveraGaxiola et al, 2000a;Werker & Lalonde, 1988). Training-related improvement has been previously shown using naturalistic versions of this contrast in English speakers, but mainly under conditions that place relatively fewer demands on working memory, for example with the use of an AX discrimination task with a relatively short inter-stimulus interval (ISI), or with the use of truncated stimuli (Pruitt, Jenkins, & Strange, 2006;Pruitt et al, 1990;Werker & Logan, 1985;Werker & Tees, 1984b). Other studies, however, have not successfully shown training-related improvement in the perception of this contrast (Tees & Werker, 1984;Werker & Tees, 1984a;Werker et al, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Jaeger 1980;Ohala 1982;Dupoux et al 1997;Harnsberger 2001;Peperkamp et al 2003;Kazanina et al 2006;Pruitt et al 2006;Boomershine et al 2008). It has been hypothesized that the reason for this difference in perception is linked to the predictability of the distribution of such sounds (Hall 2009(Hall , 2011.…”
Section: Distributionmentioning
confidence: 99%